Pengaruh Model Pembelajaran Inkuiri Terbimbing Terhadap Hasil Belajar Pada Materi Ikatan Kimia Di Man Model 1 Manado - Soenandar Milian Tompunu Tengker; Dhysa Mentari Sulistyaningsih (Oxygenius Journal Of Chemistry Education, 2020)
the purpose of this study is to there is influence average learning outcomes students who follow learning to use with those who do not use the guided inquiry model. this research was conducted in class X MAN MODEL 1 MANADO odd semester of the school year 2019/2020. this research is using an experimental method by sampling obtained class X mipa 8 as a 9 as a control class. data collection using learning outcomes test. value is with thitung 3,62 > ttabel 2,011. this means that there is a significant influence on chemical bonding material.